Prediction of recombinant Mycobacterium tuberculosis α-crystallin oligomer chaperone activity using polynomial graphs [version 1; peer review: 2 approved] - Gautam Krishnan; Utpal Roy (F1000Research, 2018)
Background: Mycobacterial α-crystallin (Acr) is a chaperone that prevents misfolding of proteins when Mycobacterium tuberculosis is found in a latent form in the host tissue. Methods: Using insulin as a model substrate and utilizing polynomial graphs, we attempted to predict molecular-level interactions that are a function of the oligomeric state of the recombinant protein. The chaperone activity of the recombinant oligomeric Acr was measured at 60°C with Acr samples obtained before gel filtration chromatography and compared with a gel-filtered sample. Results: The polynomial graphs constructed showed improved molecular coverage of the insulin B chain by the oligomer. The 2nd order coefficient is the one that changes with the oligomeric ratio of Acr and improves chaperone activity. Polynomial analysis suggested that it could be a useful parameter to predict chaperone activity for potential in vitro batches of M. tuberculosis Acr based on the dynamic nature of the association and disassociation of oligomers. Conclusions: The results showed that coverage of insulin B chain improved with higher ratio of 9-mer as compared to lower ratios. This was shown by both simulation plots and actual assay data. The polynomial graphs showed increase in the 2nd order coefficient, thus suggesting the important role of oligomerisation in improved molecular coverage of insulin B chain.